Interpretasi Semiotika Loyalitas Suami Isteri Dalam Q.S. Al-Lahab - Jendri Jendri; Ummi Kalsum (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This paper aims to describe (tell) about the loyalty of husband and wife contained in the letter al-Lahab using the semiotic approach introduced by Roland Barthes. This study uses amethodology (library researchlibrary research), and is qualitative in nature, because data collection is obtained using textual analysis contained in the letter al-Lahab. As for the results of this study are the first in the first level heuristic study contained in QS. al-Lahab verses 1-5 are of moral significance, namely the loyalty of sumai and wife. The two retroactive readings in Surat al-Lahab are about ugliness so that they lead to loss, humiliation and destruction. The third then the philosophical values are found to be the most important lessons in the interpretation of QS. al-Lahab, it is the wife's loyalty and devotion to her husband and also the husband's loyalty to his wife. But it exemplifies partner loyalty on the downside. That's why QS content. al Lahab condemns both.